Apoptotic Cells Induced Signaling for Immune Homeostasis in Macrophages and Dendritic Cells - Trahtemberg, Uriel; Mevorach, Dror (Frontiers in Immunology, 2017)
Inefficient and abnormal clearance of apoptotic cells (efferocytosis) contributes to systemic autoimmune disease in humans and mice, and inefficient chromosomal DNA degradation by DNAse II leads to systemic polyarthritis and a cytokine storm. In contrast, efficient clearance allows immune homeostasis, generally leads to a non-inflammatory state for both macrophages and dendritic cells (DCs), and contributes to maintenance of peripheral tolerance. As many as 3×108 cells undergo apoptosis every hour in our bodies, and one of the primary ‘eat me’ signals expressed by apoptotic cells is phosphatidylserine. Apoptotic cells themselves are major contributors to the ‘anti-inflammatory’ nature of the engulfment process, some by secreting thrombospondin-1 or AMP and possibly other immune modulating ‘calm-down’ signals that interact with macrophages and DCs. Apoptotic cells also produce ‘find me’ and ‘tolerate me’ signals to attract and immune modulate macrophages and DCs that express specific receptors for some of these signals. Neither macrophages or DCs are uniform and each cell type may variably express membrane proteins that function as receptors for phosphatidylserine or for opsonins like complement or opsonins that bind to phosphatidylserine, like protein S and growth arrest-specific 6. Macrophages and DCs also express scavenger receptors, CD36, and integrins that function via bridging molecules such as thrombospondin 1 or milk fat globule-EGF factor 8 protein and that differentially engage in various multi-ligand interactions between apoptotic cells and phagocytes. In this review, we describe the anti-inflammatory and pro-homeostatic nature of apoptotic cell interaction with the immune system. We do not review some forms of immunogenic cell death. We summarize the known apoptotic cell signaling events in macrophages and DCs that are related to toll-like receptors, nuclear factor kappa B (NF-κB), inflammasome, the lipid activated nuclear receptors, Tyro3, Axl, and Mertk receptors, as well as induction of signal transducer and activator of transcription 1(STAT1) and suppressor of cytokine signaling (SOCS) that lead to immune system silencing and DC tolerance. These properties of apoptotic cells are the mechanisms that enable their successful use as therapeutic modalities in mice and humans in various autoimmune diseases, organ transplantation, graft versus host disease, and sepsis.